2010
DOI: 10.1016/j.jmb.2010.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Specificity for Homooligomer versus Heterooligomer Formation in Integrin Transmembrane Helices

Abstract: Transmembrane helices engage in homomeric and heteromeric interactions that play essential roles in folding and assembly of transmembrane proteins. However, features that explain their propensity to interact homomerically or heteromerically and determine the strength of these interactions are poorly understood. Integrins are an ideal model system to address these questions because the transmembrane helices of full-length integrins interact heteromerically when integrins are inactive, but the isolated transmemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…1A) and applied a similar method to determine whether the ␣IIb or ␤3 TM domains form homo-oligomers during integrin signaling. As suggested by the TOXCAT assay (24,25) and predicted by computer modeling (26 -28), the ␣IIb TM helix forms homodimers, and the ␤3 TM helix forms homotrimers, using surfaces that are similar to those in the heterodimeric interface. If this homomeric interface is actually formed in the mammalian cell membrane, we expected that some singlecysteine mutations of these residues would form homodimeric disulfide bonds in the presence of an oxidation catalyst such as Cu-phenanthroline.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…1A) and applied a similar method to determine whether the ␣IIb or ␤3 TM domains form homo-oligomers during integrin signaling. As suggested by the TOXCAT assay (24,25) and predicted by computer modeling (26 -28), the ␣IIb TM helix forms homodimers, and the ␤3 TM helix forms homotrimers, using surfaces that are similar to those in the heterodimeric interface. If this homomeric interface is actually formed in the mammalian cell membrane, we expected that some singlecysteine mutations of these residues would form homodimeric disulfide bonds in the presence of an oxidation catalyst such as Cu-phenanthroline.…”
Section: Resultsmentioning
confidence: 96%
“…Instead, they observed that the ␣ and ␤ fragments tend to form homodimers and homotrimers, respectively (23). Later, ␣IIb and ␤3 TM helices were confirmed to form homo-oligomers in bacterial membranes using the TOXCAT assay (24,25). The ␣ and ␤ homomeric interactions have been widely studied by computational modeling (26 -28).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The functional significance of TMDs and their mechanisms of assembly have previously been demonstrated for many membrane proteins including integrins, receptor tyrosine kinases and G-protein coupled receptors [78][79][80]. Several biochemical studies have emphasized the functional relevance of TMD interactions and their regulation [81][82][83][84] in the TLR family.…”
Section: Tlr Transmembrane Domainsmentioning
confidence: 99%